Quantitative profile of lipid classes in blood by normal phase chromatography with evaporative light scattering detector: Application in the detection of lipid class abnormalities in liver cirrhosis - Chamorro, Laura; García-Cano, Ana; Busto, Rebeca; Martínez-González, Javier; Albillos, Agustín; Lasunción, Miguel Ángel; Pastor, Óscar (Clinica chimica acta, 2013)
The lack of analytical methods specific for each lipid class, particularly for phospholipids and sphyngolipids, makes necessary their separation by preparative techniques before quantification. LC–MS would be the election method but for daily work in the clinical laboratory this is not feasible for different reasons, both economic and time consuming. In the present work, we have optimized an HPLC method to quantify lipid classes in plasma and erythrocytes and applied it to samples from patients with cirrhosis. Lipid classes were analyzed by normal phase liquid chromatography with evaporative light scattering detection. We employed a quaternary solvent system to separate twelve lipid classes in 15min. Interday, intraday and recovery for quantification of lipid classes in plasma were excellent with our methodology. The total plasma lipid content of cirrhotic patients vs control subjects was decreased with diminished CE (81±33 vs 160±17mg/dL) and PC (37±16 vs 60±19mg/dL). The composition of erythrocytes showed a decrease in acidic phospholipids: PE, PI and PS. Present methodology provides a reliable quantification of lipid classes in blood. The lipid profile of cirrhotics showed alterations in the PC/PE plasma ratio and in the phospholipid content of erythrocytes, which might reflect alterations in hepatocyte and erythrocyte membrane integrity. ► There is a lack of methodologies to get a full profile of lipid classes in blood. ► We optimized an HPLC–ELSD to quantify lipid classes in human blood. ► We compare the lipid class profile in blood of cirrhotics and healthy controls. ► We found alterations in the PC/PE ratio measured in plasma of cirrhotics. ► We described alterations in erythrocyte acidic phospholipids of cirrhotics.